Селекционно-генетическое изучение хозяйственных признаков хлопчатника и методы повышения эффективности отбора - Асадов, Ш.И.; Гусейнова, Л.А.; Абдулалиева, Г.С.; Юнусова, Ф.М. (Фактори експериментальної еволюції організмів, 2013)
Aims. Studying of mutants of a cotton and hybrids of a mutant origin to the important signs, and also allocation of the constant forms having practical and theoretical value. Methods. As object of research grades of a cotton of variety Gossypium hirsutum L. served from a collection of Institute of Genetic Resources NАS of Azerbaijan. For expansion of a range of a genetic variety research spent to two stages: at first used experimental mutagenesis for reception of mutants, then mutants with alternative signs included in hybridization. Results. Genetically pure lines, having passed all stages of selection process, are finished to competitive test. The tentative estimation of a studied selection material in competitive nursery has allowed to reveal perspective grades Карабах-2, Карабах-3 and Агдаш-22, characterised by a complex set of positive signs. Conclusions. The perspective grades, successfully passed competitive test, are transferred for check in the State Commission of Azerbaijan.

Key words: a cotton, mutagenesis, hybridization, quality of a fiber, efficiency, creation of grades.